Perioperative crisis resource management simulation training in anaesthesia - Dinker R Pai; V R Hemanth Kumar; R Sobana (Indian Journal of Anaesthesia, 2024)
Simulation-based education is now recognised to be a valuable tool to impart both technical and non-technical skills to healthcare professionals of all levels. Simulation is an well accepted educational tool for cultivating teamwork skills among residents globally. Simulation-based education encompasses diverse modalities, ranging from task trainers and simulated patients to sophisticated high-fidelity patient simulators. Notably, anaesthesiologists globally were early advocates of integrating simulation into education, particularly to instruct anaesthesia residents about the intricacies of perioperative crisis resource management and collaborative interdisciplinary teamwork. Given the inherent high-risk nature of anaesthesia, where effective teamwork is pivotal to averting adverse patient outcomes, and also to improve overall outcome of the patient, simulation training becomes imperative. This narrative review delves into the contemporary landscape of simulation training in perioperative anaesthesia management, examining the pedagogical approaches, simulators, techniques and technologies employed to facilitate this training.